2010
DOI: 10.1093/cvr/cvq193
|View full text |Cite
|
Sign up to set email alerts
|

Down's syndrome-like cardiac developmental defects in embryos of the transchromosomic Tc1 mouse

Abstract: AimsCardiac malformations are prevalent in trisomies of human chromosome 21 [Down's syndrome (DS)], affecting normal chamber separation in the developing heart. Efforts to understand the aetiology of these defects have been severely hampered by the absence of an accurate mouse model. Such models have proved challenging to establish because synteny with human chromosome Hsa21 is distributed across three mouse chromosomes. None of those engineered so far accurately models the full range of DS cardiac phenotypes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 44 publications
4
48
0
Order By: Relevance
“…We and the others have shown that the triplication of the Cbr1-Fam3b does not cause heart defects in the Ts1Rhr embryos (Fig. 1) (Dunlevy et al 2010; Liu et al 2011b). Because of the presence of a 1.6-Mb overlapping duplicated region between Dp(16)4Yey and Ts1Rhr, which carries 14 Hsa21 gene orthologs (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…We and the others have shown that the triplication of the Cbr1-Fam3b does not cause heart defects in the Ts1Rhr embryos (Fig. 1) (Dunlevy et al 2010; Liu et al 2011b). Because of the presence of a 1.6-Mb overlapping duplicated region between Dp(16)4Yey and Ts1Rhr, which carries 14 Hsa21 gene orthologs (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Studies investigating the penetrance and variability in DS phenotypes have previously singled out nontrisomic genes as important factors in DS phenotypes (Epstein 2001;Kerstann et al 2004). For example, nontrisomic CRELD1 mutations have been linked to an increased penetrance of atrioventricular septal defects in individuals with DS, and the occurrence of DS-like heart defects in the Tc1 DS mouse model were dependent upon genetic background (Maslen et al 2006;Dunlevy et al 2010). Certain alleles of GATA1, also not found on Hsa21, may predispose individuals with Ts21 to DS-related acute megakaryoblastic leukemia (Wechsler et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also suggest the potential contribution of VEGFA (Ackerman et al 2012), ciliome and Hedgehog (Ripoll et al 2012), and folate (Locke et al 2010) pathways to the pathogenicity of CHD in DS. There are also several mouse models for partial or complete trisomy syntenic to human chromosome 21 (Sago et al 1998;Shinohara et al 2001;Dunlevy et al 2010;Yu et al 2010). CHDs have been observed in the full ''trisomy 21'' homologous mice Tc1 (Dunlevy et al 2010) and Dp(10)1Yey/+; Dp(16)1Yey/+; Dp(17)1Yey/+ mice (Yu et al 2010).…”
mentioning
confidence: 99%
“…There are also several mouse models for partial or complete trisomy syntenic to human chromosome 21 (Sago et al 1998;Shinohara et al 2001;Dunlevy et al 2010;Yu et al 2010). CHDs have been observed in the full ''trisomy 21'' homologous mice Tc1 (Dunlevy et al 2010) and Dp(10)1Yey/+; Dp(16)1Yey/+; Dp(17)1Yey/+ mice (Yu et al 2010). In addition, CHDs have been observed in the partial ''trisomy 21'' model Ts65Dn that is trisomic for 13.4 Mb of the 22.9-Mb chromosome 21 syntenic regions (Moore 2006;Williams et al 2008).…”
mentioning
confidence: 99%